DETERMINAN PERSISTENSI LABA PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE DI BEI 2018-2022 - Susilowati, Pusvita Indria Mei; Quddus, Noor Malik (Jurnal Riset Akuntansi Politala, 2024)
This study aims to identify and analyze the impact of accrual amounts, book tax differences, revenue growth, and debt levels on earnings persistence. The independent factors examined in this study include accrual amounts, book tax differences, income growth, and debt levels. Meanwhile, the variable that depends on these factors is earnings persistence. This research was conducted on property and real estate sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The research sample was selected using a purposive sampling method, with a total of 15 companies that meet certain criteria. Data analysis was performed using multiple regression methods through SPSS version 26 software. The results showed that revenue growth has a positive effect on earnings persistence. However, accrual amounts, book tax differences, and debt levels do not have a significant impact on the persistence of earnings in property and real estate sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period.